An Assessment of Coastal Vulnerability of Pahangâ€™s Coast Due to Sea Level Rise - Amri Mohd, Fazly; Nizam Abdul Maulud, Khairul; A. Karim, Othman; Ara Begum, Rawshan; Firoz Khan, Md; Shafrina Wan Mohd Jaafar, Wan; Mastura Syed Abdullah, Sharifah; Ekhwan Toriman, Mohd; Khairul Amri Kamarudin, Mohd; Barzani Gasim, Muhammad; Abd Wahab, Noorjima (International Journal of Engineering and Technology, 2018)
Climate change interacts in a different way with varieties of human activities and other drivers of change along coastlines. Sea level rise (SLR) is one of the major impacts of global warming. Changes in climate extremes and SLR may impact the critical infrastructures such as coastal road, jetty and chalets as well as the local community. The population and assets exposed to coastal risks will increase significantly due to population growth, economic development and urbanization in the future. As most of the cities in Malaysia are situated near the coast, immediate actions are needed to minimize the undesired outcome due to the SLR. The main objective of this study is to identify physical variables that may have impacts on the coastal area, thus develop a coastal vulnerability index (CVI) for the East Coast of Peninsular Malaysia. Seven (7) physical variables have been identified to assess the CVI that consists of geomorphology, coastal slope, shoreline change rate, mean significant wave height, mean tidal range, relative sea level rate and land use. A comprehensive CVI was obtained by integrating the differential weighted rank values of the variables. The outcome of this study is useful as a tool for coastal disaster management.Â Â